Annotations for Streaming Video on the Web: System Design and Usage Studies - Bargeron, David; Grudin, Jonathan; Gupta, Anoop; Sanocki, Elizabeth (Elsevier, 1999)
Streaming video on the World Wide Web is being widely deployed, and workplace training and distance education are key applications of the technology. The ability to annotate video presentations on the Web can provide significant added value to these applications. Written and spoken annotations can provide “in context” personal notes and enable asynchronous collaboration, turning passive internet media content into interactive, living content. We discuss design considerations in constructing a collaborative video annotation system and introduce our prototype, called MRAS. We present preliminary data on use of MRAS for personal note-taking and for sharing notes. The subjects in our studies showed a strong preference for using MRAS to take notes (although it took longer to do so), as compared to pen-and-paper. The subjects also indicated they would make more comments and questions with MRAS than in a “live” class, and that sharing added substantial value. We also discovered some surprising results with respect to usability aspects of a video-annotation system.